ZnHCF@PB nanoparticles with reduced bandgap as a promising photocatalyst for the degradation of conventional and emerging water contaminants - Fatima, Hira; Azhar, M.R.; Cao, Chencheng; Shao, Zongping (2023)
The photocatalytic degradation of conventional and emerging pollutants (i.e., methyl, ethyl, and butyl parabens) was investigated under light irradiation with 315–1050 nm wavelength using core–shell zinc doped hexacyanoferrate@Prussian blue nanoparticles. Different synthesis parameters including precursors loading, drying temperature and different metal ions precursors were studied. The ten different composite systems obtained, were investigated for the photodegradation of methylene blue in deionized water. The optimal performance photocatalyst (20 mg/L) photodegrade 94% of 10 ppm methylene blue within 24 min. The optimized sample was further used for the photodegradation of methylene blue in municipal wastewater matrix; it completely degraded the methylene blue after 51 min. Finally, the developed nanoparticles were investigated for the photodegradation of parabens. The chemical oxygen demand showed 30% of parabens was degraded in the municipal wastewater matrix. The results of this research show that ZnHCF@PB nanoparticles could be used for the effective photocatalytic remediation of conventional and emerging pollutants, i.e., parabens. Statement of environmental implication: Through this study, it is anticipated that ZnO-derived ZnHCF@PB NPs can achieve a bandgap of 1.11 eV, which is much lower than that of ZnO NPs (3.15 eV). Interestingly, ZnHCF@PB NPs were efficiently used for the degradation of conventional (i.e., dyes) and emerging contaminants (i.e., parabens) in deionized water and municipal wastewater matrices to mimic industrial wastewater.